Yeah, that’s it!: Verbal Reference to Visual Information in Film Texts and Film Translations - Baumgarten, Nicole (Meta, 2008)
AbstractThis article presents an account of the meaning relationship between visual and verbal information in film and the differences between the conventions of making verbal reference to visual information in English films and their German-language versions. The analysis of a diachronic corpus of popular motion pictures and their German-dubbed versions indicates that the film translations ‘handle’ the co-occurring visual information differently than their English source texts. The translations tend to use alternative, non-equivalent, linguistics structures to refer to visual information and insert additional pronominal references and deictic devices, which overtly connect linguistic items to pictorial elements. As a result, the ongoing spoken discourse is explicitly linked with the physical surroundings of the communicative encounter. In contrast, in the English language versions, the relationship between the verbal utterance and the accompanying visual information more often remains lexically implicit. The shifts in translation affect the ideational, interpersonal, and textual meanings expressed in the film texts which, in turn, may result in a variation in the films’ narrative construction and the realization of extralinguistic concepts, such as, for example, gender relations.